A novel coupling approach for determination of stress intensity factor for bi-material Reissner plates under bending or twisting. (December 2022) - Yu, Xiong; Yang, Zhenting; Zhang, Quanquan; Tong, Zhenzhen; Zhou, Zhenhuan; Xu, Xinsheng
Highlights: A novel coupling approach is proposed for interface-cracked Reissner plates in bending or twisting. The coupling approach are developed based on an eigenfunction expansion method and IGA. Explicit expressions of SIFs and singular stresses around the crack tip are obtained simultaneously. Abstract: A novel coupling approach is proposed to determine stress intensity factors (SIFs) for interface cracks in bi-material Reissner plates under bending or twisting. The Reissner plate theory is adopted to derive asymptotic solutions around the crack tip and T-spline functions are introduced to establish the model. The approach has two major steps. Firstly, the overall cracked plate is divided into two regions (near and far fields) and is discretized by the T-spline based isogeometric analysis (IGA). Subsequently, the large number of fundamental unknowns of control points in the near field is reduced into a small set of undetermined coefficients of asymptotic solutions obtained by the eigenfunction expansion method. Therefore, explicit expressions of SIFs and singular stress components near the crack tip are obtained simultaneously. A number of numerical examples for various cracks laying at the interface are presented, and are found to be in good agreement with available solutions.